“Connecting With Good People and Good Plants”: Community Gardener Experiences in New York State During the COVID-19 Pandemic - Falkowski, Tomasz B.; Jorgensen, Bethany; Rakow, Donald A.; Das, Ashmita; Diemont, Stewart A. W.; Selfa, Theresa; Arrington, Austin B. (Frontiers in Sustainable Food Systems, 2022)
Community gardens are collective projects in which participants collaborate to maintain a garden. They provide many biophysical and cultural ecosystem services, contributing to individual and community resilience and well-being. These benefits may be even more appreciated during a crisis such as the COVID-19 pandemic. However, since community gardens require efforts from multiple gardeners in shared spaces, the pandemic also exposed some of their vulnerabilities. This study focuses on the benefits community gardens have offered during the COVID-19 pandemic, the challenges the pandemic posed to sustaining community garden activity, and recommendations to address these issues moving forward. We conducted our study in four cities in New York representing a gradient of socioeconomic and biophysical characteristics: Binghamton, Buffalo, Ithaca, and New York City. We collected data from surveys and semi-structured interviews with community gardeners and analyzed them using mixed models and thematic coding. The primary benefits gardeners derived from their community garden experiences were: a sense of connection with other gardeners, their communities, and nature; mental and physical well-being; and a safe space of refuge. In addition to material shortages (e.g., seeds), the biggest challenge gardeners faced due to the pandemic was the limited degree of socializing in the gardens resulting from personal behavioral changes and rules imposed by gardens. Despite the challenges, gardeners reported enjoying the 2020 garden season. The pandemic also created opportunities for gardens to serve their communities, such as organizing programs for composting, food donation and distribution, and home gardening. Our findings suggest that community gardens can be resilient sites of reprieve during crises such as the COVID-19 pandemic, providing essential benefits for gardeners and local residents. To sustain community garden resilience, we recommend community gardens and gardeners cultivate connections and diversity, within and between the biological and human communities of their gardens.